Analysis of The Semiotics of Roland Barthes: In The "Ari Irham" Version of The Palm Sugar Coffee Advertisement - Hia, Yuniarti; Azis, Abdul (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2024)
This study aims to examine the meaning contained in Ari Irham's version of the "Gula Palm" coffee advertisement using the semiotics theory of Roland Barthes. The approach used is qualitative descriptive with a semiotic perspective. The data analyzed includes visual, text, and sound elements in the ad. The findings of the study show that the "Gula Aren" coffee advertisement contains denotative, connotative, and mythical meanings related to the themes of love, happiness, and health. In addition, these ads use persuasive strategies to attract consumers' attention, by taking advantage of the popularity of young celebrities as endorsers.